Keratinocytic epidermal nevus with ipsilateral breast hypoplasia - Eric Chen, BS; Anthony J. Chiaravalloti, MD; Justin Finch, MD (Wolters Kluwer, 2019)
Breast hypoplasia has been reported in some epidermal nevus syndromes, but not with a keratinocytic epidermal nevus. Herein, we describe the first case of breast hypoplasia associated with a keratinocytic epidermal nevus. Keratinocytic epidermal nevi have been shown to be associated with somatic mutations in FGFR3, PIK3CA, and HRAS. We hypothesize that hypoplasia may be due to a local mutation in the FGFR3 gene or increased androgen receptors in affected breast tissue. The patient was treated with CO2 laser with good cosmetic outcome. Keywords: Keratinocytic epidermal nevus, ipsilateral breast hypoplasia, FGFR3